Distal transradial artery access in the anatomical snuffbox for coronary angiography as an alternative access site for faster hemostasis. Issue 5 (24th February 2019) - Aoi, Shunsuke; Htun, Wah Wah; Freeo, Stephanie; Lee, Samuel; Kyaw, Htoo; Alfaro, Victor; Coppola, John; Pancholy, Samir; Kwan, Tak
Abstract: Objectives: This study investigated the feasibility, safety, and the potential benefit of faster hemostasis with the distal transradial artery access (TRA). Background: TRA has been shown to be associated with lower bleeding and vascular complications. Limited data are available regarding the new technique of accessing the distal radial artery in the anatomical snuffbox. Methods: We retrospectively reviewed 202 consecutive patients who underwent coronary angiography and intervention with distal TRA. Two hundred and six conventional TRA cases were collected as a comparison arm. Results: Out of 408 patients, successful distal radial access was obtained in 99.5% (201/202) in the distal TRA cases and 99.0% (204/206) in the conventional TRA cases. The rate of access site crossover was 2.0% (4/202) for distal TRA. Right distal radial artery was accessed in 176 cases (87.6%). Mean access time from local anesthesia to radial flush was 7.3 min. Ninety cases (44.8%) were percutaneous coronary interventions (PCIs) and the mean heparin dose used was 4, 448 units (6, 009 units for PCI and 3, 182 units for diagnostic catheterization). Mean time to remove TR band was 104.7 min (120.8 min for PCI and 91.7 min for diagnostics). Follow‐up ultrasound study showed two partial occlusions (1.0%) and one arteriovenous fistula (0.5%) that resolved with prolonged TR band inflation. Conclusions: Despite longer time to access the distal radial artery in the anatomical snuffbox, it is a safe and feasible alternative to conventional TRA and might result in shorter time to hemostasis especially in cases of PCI.